Economic aspects of subjective attitudes towards the minimum wage reform - Alexandra Fedorets; Carsten Schröder (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
Despite some skepticism among experts about the effects of a minimum wage, there is remarkably widespread public support for such policies. Using representative survey data from 2015 and 2016, we investigate the subjective attitudes driving public support for Germany's recent minimum wage reform. We find that socio-economic characteristics and political orientations explain a minor part of the variation in attitudes, whereas beliefs that the reform will bring positive redistributional effects and perceptions that it will help people to maintain or improve their overall economic situation (measured by living standards, income, hours worked, and job security) play a major role.
Keywords: D71; E64; J38; 330; Public Opinion; Public Policy; Minimum Wage Reform